Is the VO2max that we measure really maximal? - Smirmaul, B. P. C.; Bertucci, D. R.; Teixeira, I. P. (Frontiers in Physiology, 2013)
The maximal oxygen uptake (VO2max) can be defined as the maximum integrated capacity of the pulmonary, cardiovascular and muscular systems to uptake, transport and utilize O2, respectively (Poole et al., 2008). Usually measured by the incremental exercise test in the treadmill or cycle ergometer, the VO2max test has become a cornerstone in clinical and applied physiology involving physical exercise. Its applications are numerous, ranging from elite athletes to individuals with several pathologic conditions (Mancini et al., 1991; Bassett and Howley, 2000). Despite studied for approximately a century, questions regarding the VO2max are still source of debate and disagreement in the literature (Noakes, 1998; Bergh et al., 2000; Levine, 2008; Ekblom, 2009; Noakes and Marino, 2009; Spurway et al., 2012). In particular, the study of the methods of VO2max measurement is a field of investigation that has been challenging through the years (Midgley et al., 2007, 2008). Intriguing findings recently published (Beltrami et al., 2012; Mauger and Sculthorpe, 2012) bring additional debate regarding the measurement of the true VO2max value and its limiting/regulatory mechanisms. In this article we briefly describe the current testing methods and mechanisms of VO2max limitation/regulation, and discuss the new findings of these two recent studies and their possible implications in the field.